Knoglerne fra Kassø - Fichte, Almut (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
The excavations in Kassø in 2017 – 2018 covered 51.4 ha land. Among the excavations were the remains of two barely visible Bronze Age burial mounds as well as an early Roman Iron Age cremation burial site with an adjoining, contemporary settlement. Several of the individuals buried at the cremation cemetery site seem to be young to middle aged men; there are no clearly identified women and only few children, including one infant. The individuals carried a few pathological markers, some of them showing signs of arthritis, some possible genetic dental pathology, one individual showed signs of malnutrition in childhood, and another showed possible signs of a rich carbohydrate diet. Many of the graves also contained animal bones, almost exclusively of sheep/goat and mostly just a single lower leg. Furthermore, most of the represented grave goods are knives and parts of the belt, whereas four to five graves contained parts of weapons and shields. The six graves from the Bronze Age mounds have not yielded as much information as the Early Roman Iron Age cremation burial site. Most individuals were merely identified as adults, and none could be sexed. Nor did they show signs of pathology. However, two of the graves contained more than one person. Grave goods were only found in graves dating to the Early Bronze Age and comprised mostly adornments such as arm and neck rings and tutuli.